2023
DOI: 10.1038/s41598-022-27292-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between levels of exposure to heavy metals and renal function indicators of residents in environmentally vulnerable areas

Abstract: Abandoned metal mines and refineries are considered environmentally vulnerable areas owing to high levels of exposure to heavy metals. This study examined the association between heavy metal exposure and renal function indicators. We studied a total of 298 participants, of which 74 and 68 resided in low- and high-exposure abandoned metal mine areas, respectively, with 121 in the refinery area and 35 in the control area. Blood and urine samples were collected from the participants to analyze the levels of blood… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 37 publications
0
1
2
Order By: Relevance
“…In this study we employed multifactorial regression to investigate the association between serum metals and CKD. Interestingly, our findings diverged significantly from previous studies ( 13 , 14 ), which could be attributed to geographic variations, differences in dietary habits, lifestyles, and environmental conditions ( 15 ) across different regions. Through LASSO regression analysis, we identified a positive association between Na and CKD, even after adjusting for covariates such as general characteristics and routine blood markers.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study we employed multifactorial regression to investigate the association between serum metals and CKD. Interestingly, our findings diverged significantly from previous studies ( 13 , 14 ), which could be attributed to geographic variations, differences in dietary habits, lifestyles, and environmental conditions ( 15 ) across different regions. Through LASSO regression analysis, we identified a positive association between Na and CKD, even after adjusting for covariates such as general characteristics and routine blood markers.…”
Section: Discussioncontrasting
confidence: 99%
“…Their sample was of women 18–44 years old living around Buffalo, New York, USA. Contrasting our results, Kwon et al (2023) found an association with CdB and decreased eGFR, but not PbB, in their low-exposure group compared to their reference group [ 40 ]. The authors examined the relationship of lead exposure on renal function in 298 individuals, 70.3 years old on average.…”
Section: Discussioncontrasting
confidence: 99%
“… 21 , 45 , 46 , 47 , 48 , 49 Indeed, arsenic, cadmium, and lead are pervasive toxicants with established mechanisms for inducing both acute kidney injury and CKD, resulting in ongoing investigations into potential contributions to the epidemics of CKDu occurring worldwide. 50 , 51 Although some association of heavy metals have been made with increased risk of CKDu, such findings have been inconsistent. 23 , 24 Thus, it is unsurprising that elemental analysis found that urinary levels of heavy metals were relatively low and did not increase significantly over the harvest.…”
Section: Discussionmentioning
confidence: 99%